Improving the efficiency of multimodal transportation of chemical products from the Volgograd region to the near and far abroad - A. V. Kulikov; P. A. Pavlov; A. A. Kulikov (Вестник СибАДИ, 2023)
Introduction. The industrial sector of Russia is the most important segment of the country’s economy. Until the beginning of the 21st century, large chemical enterprises in Russia were focused on the domestic market. There was a so-called supply strategy formed back in the USSR for the Union Socialist republics. The products of the chemical industry were mainly transported by road around the city and to neighboring regions, the main cargo traffic for longer distances was mastered by rail and river transport. Currently, the largest chemical industry enterprise in the Volgograd region, AO Kaustik, is actively exporting to Europe, South America and Asia. To carry out international transportation of the company’s products, hired tractors with semi-trailers that meet all modern standards of environmental safety are used. The interaction of road transport with rail, river, and sea is actively taking place, effective logistics multimodal systems for the delivery of chemical products are being organized. Road and rail transportation of products is organized with Asian countries, with European countries – by road, rail and sea, with South American countries – by sea. Today, the company’s transport carries out international multimodal transportation to the near and far abroad. The issue of improving the efficiency of road transport is relevant. The paper considers the links of the logistics system of transportation of chemical products of the enterprise between the countries, along the routes: Russia – Netherlands and Russia – Kyrgyzstan. The comparison of road and rail transportation by time and cost on Volgograd – Bishkek route is carried out. The full loading of the vehicle with transport packages according to the calculation takes place in compliance with the loads on the axles of the tractor and semi-trailer. Improving the efficiency of transportation depends on the organization of loading and unloading points, customs control points, movement along routes, and the work of drivers. The statistical regularities of the distribution of the execution time of elements and operations in the loading point of the enterprise are investigated. The ways of organizing the work of motor transport drivers on the international Volgograd – Bishkek – Volgograd route are considered, the calculation of the duration of the elements of the transportation process and their cost is presented.Materials and methods. The paper uses methods of statistical and economic analysis of data on the functioning of the chemical industry in the region. Graph-analytical methods are used to form transport packages and ensure that the car is fully loaded. Methods for determining the shortest distances and drawing up routes on the transport network are used. Methods of organizing the work of drivers are used to ensure single and tour work on the international route. The effectiveness of the proposed measures is evaluated by economic methods.Results. It is revealed that the chemical industry of the region has a stable economic situation that allows it to develop new international markets. The links of the multimodal logistics system for the delivery of the company’s products along Volgograd – Bishkek and Volgograd – Netherlands international routes are investigated. Improving the efficiency of transportation depends on the organization of loading and unloading points. A statistical analysis of the elements and stages of the transportation process of caustic soda was carried out. A scheme for placing transport packages with bags of caustic soda in a semi-trailer of a motor vehicle has been developed. International routes of transportation of products of AO Kaustik using road transport have been developed: Volgograd – Bishkek and Volgograd – Netherlands routes. The mode of operation of motor transport when performing international transportation using tour and single organization of drivers’ work is calculated. We recommend a tour trip as the most effective way to organize the work of drivers. Tour riding is recommended as the most effective way of organizing the work of road transport in the organization of international transportation to near and far abroad. The final price of 1 ton of transported products on the Volgograd – Bishkek route has been determined. The effective functioning of road transport in the international logistics system for the delivery of caustic soda allows you to reduce transport time, transport costs and reduce the cost of a unit of production for the end user.Conclusions. The article develops measures to improve the organization of international transportation of products of JSC «Caustic» using road transport. The final price of 1 ton of products in the Bishkek warehouse, taking into account the initial cost of granular caustic soda and transportation costs in the case of organizing a single driver’s ride, will be 83246 rubles/ton, and for tour driving, respectively, 81355 rubles/ton.